Long-Term White Matter Changes after Severe Traumatic Brain Injury: A 5-Year Prospective Cohort - Dinkel, J.; Drier, A.; Khalilzadeh, O.; Perlbarg, V.; Czernecki, V.; Gupta, R.; Gomas, F.; Sanchez, P.; Dormont, D.; Galanaud, D.; Stevens, R.D.; Puybasset, L.; et al. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: Extensive white matter damage has been documented in patients with severe traumatic brain injury, yet how this damage evolves in the long term is not well understood. We used DTI to study white matter changes at 5 years after traumatic brain injury. MATERIALS AND METHODS: There were 8 healthy control participants and 13 patients with severe traumatic brain injury who were enrolled in a prospective observational study, which included clinical assessment and brain MR imaging in the acute setting (< 6 weeks) and 2 years and 5 years after injury. Only subjects with mild to moderate disability or no disability at 1 year were included in this analysis. DTI parameters were measured in 20 different brain regions and were normalized to values obtained in an age-matched control group. RESULTS: In the acute setting, fractional anisotropy was significantly lower in the genu and body of the corpus callosum and in the bilateral corona radiata in patients compared with control participants, whereas radial diffusivity was significantly (P < .05) higher in these tracts. At 2 years, fractional anisotropy in these tracts had further decreased and radial diffusivity had increased. No significant changes were detected between 2 and 5 years after injury. The baseline radial diffusivity and fractional anisotropy values in the anterior aspect of the brain stem, genu and body of the corpus callosum, and the right and left corona radiata were significantly (P < .05) associated with neurocognitive sequelae (including amnesia, aphasia, and dyspraxia) at year 5. CONCLUSIONS: DTI changes in major white matter tracts persist up to 5 years after severe traumatic brain injury and are most pronounced in the corpus callosum and corona radiata. Limited structural change is noted in the interval between 2 and 5 years. FAfractional anisotropyL1axial diffusivityLtradial diffusivityMDmean diffusivityTBItraumatic brain injury